Peningkatan Keamanan Ssh Dengan Port Knocking Berbasis Rsa Dan Verifikasi Otp Pada Server Data Personel Militer: Rekayasa Keamanan Siber - Andika Edwin Baskoro; Heri Setiawan; Asep Suryanta (Jurnal Telkommil, 2026)
Securing access to servers that store military personnel data is essential to maintain the confidentiality, integrity, and availability of sensitive information within defense institutions. Servers that manage strategic data are often targeted by unauthorized users, making the implementation of a layered security mechanism necessary. Secure Shell (SSH) is commonly used for remote server access. However, if it is configured using default settings, SSH may become vulnerable to attacks such as brute-force attempts and port scanning. These attacks are frequently used by attackers to identify open ports and attempt unauthorized login access. One technique that can be used to improve server security is Port Knocking, which hides service ports from public scanning by requiring a specific sequence of connection attempts before access is granted. Although this technique can reduce the exposure of open ports, a static knocking pattern may still be discovered by attackers. This research proposes an SSH security system that integrates RSA-based port knocking with One-Time Password (OTP) verification as a two-factor authentication mechanism. The RSA algorithm is used to encrypt the knocking sequence so that the access pattern becomes difficult to predict. Meanwhile, OTP verification ensures that only authorized users can complete the authentication process. The study was conducted using an experimental approach within a server environment. The results show that the proposed system can significantly reduce unauthorized access attempts while maintaining acceptable system performance.